The Android Application Provides Futsal Sports Physical Condition Test Results for Individuals Aged 18-40 years - Bagas Bintang Prakoso; Andri Irawan; Eko Prabowo (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objectives. This Android application exemplifies the power of science and technology to provide quick and convenient access to a wealth of information. Specifically, it was designed to streamline the process of recording athletes' physical abilities. With the goal of creating a physical condition test that can be utilized in futsal, the researcher behind this project developed an Android application that assesses the player's level of fitness and simplifies data collection for coaches. Materials and Methods. The researchers utilized the research and development method employing the ADDIE development model. This approach involved five key stages, including analysis, design, development, implementation, and evaluation. The test results yielded by the application encompassed a total of 10 test instruments, which effectively measured 7 different aspects of physical condition. Results. A team of experts developed an Android-based application for futsal enthusiasts. The application underwent validation and feasibility tests, which included reviews from technology experts, futsal physical trainers, and futsal expert lecturers. To ensure the effectiveness of the application, 18 futsal coach respondents participated in the trial. The results showed that the application had a suitability rating of 96.67%, which was deemed to be very good. The rating was based on the application's ability to meet the needs and expectations of the users. Furthermore, the application scored 94.44% for attractiveness, which was also declared very good. This rating was based on the application's user interface, design, and overall appeal to the users. Overall, the application received positive feedback from the trial participants, indicating that it was an effective tool for futsal enthusiasts. Conclusions. The results suggest that the Android application developed is a suitable tool for coaches to efficiently access the physical test results of their players. This app can potentially streamline the process of monitoring and evaluating the performance of their team and aid in making informed decisions.